Software defined network implementation of multi-node adaptive novel quantum key distribution protocol - Hardeer Kaur; Jai Sukh Paul Singh (AIMS Electronics and Electrical Engineering)
Access to information can destroy nations and change the course of history altogether. Communication is very important, and in today's internet age, nothing moves without real-time information support. For securing communication, a commonly know technique is to use cryptography and public channels. Engineers have been working to create a better and more secure cryptographic system. Quantum key distribution stands at the top of this security system. Although QKD, based on principles of physics, provides a near-perfect security solution. It has a few drawbacks of its own, like low key generation rates and vulnerability to cyberattacks. Owning to these limitations, authors propose an adaptive quantum key distribution system based on software-defined networks. The authors propose to introduce redundancy in the key generation, thereby increasing the key generation rate and improving the resilience to cyberattacks. A performance comparison of novel quantum key distribution was done with BB84 and B92 quantum key distribution protocols.